1990
DOI: 10.1679/aohc.53.193
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies on the conduction system of diabetic rat hearts.

Abstract: Summary. We studied the metabolism of the conduction system and the working myocardium in diabetic rat hearts by enzyme histochemistry. The experiment was performed three weeks following the administration of streptozotocin (65 mg/kg) to male Wistar rats. The hearts were quickly excised and tissue was frozen immediately by immersion in isopentane at -30C and cut into 16 pm thick sections in a cryostat. The PAS positive reaction was increased in the conduction system compared to the working myocardium in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Experiments in which the cortices were separated into glomerular and tubular fractions showed that both glomeruli and tubules displayed decreased G6PD activity in diabetic animals compared with NDM controls (data not shown). This observation is consistent with previously published data in which decreased G6PD activity has also been observed in liver (33), aorta (43), heart (27,42), and Leydig cells (5) from diabetic animal models. Moreover, it has been reported that patients with diabetes have decreased G6PD levels in liver (6), mononuclear leukocytes (34,44), and erythrocytes (9,10).…”
Section: Discussionsupporting
confidence: 93%
“…Experiments in which the cortices were separated into glomerular and tubular fractions showed that both glomeruli and tubules displayed decreased G6PD activity in diabetic animals compared with NDM controls (data not shown). This observation is consistent with previously published data in which decreased G6PD activity has also been observed in liver (33), aorta (43), heart (27,42), and Leydig cells (5) from diabetic animal models. Moreover, it has been reported that patients with diabetes have decreased G6PD levels in liver (6), mononuclear leukocytes (34,44), and erythrocytes (9,10).…”
Section: Discussionsupporting
confidence: 93%
“…For example in cell culture models of endothelial cells and mesangial cells, G6PD is significantly inhibited by high glucose [27]. In animal models, decreased G6PD activity has been reported in liver [28], aorta [29], heart [30], [31], and Leydig cells [32]. In diabetic patients, decreased G6PD activity has been detected in percutaneous liver biopsies [32], mononuclear leukocytes [33], [34], and erythrocytes [35], [36].…”
Section: Discussionmentioning
confidence: 99%